The Role of The English Vocabulary Level Test For ESP Learners: Assessing Students’ Readiness - Siradjuddin, Suharti; Yahrif, Muhammad (Jurnal Riset dan Inovasi Pembelajaran, 2024)
This research aims to determine the student’s readiness to learn English at the tertiary level through vocabulary tests. This research was carried out due to the low English skills at the tertiary level for English-specific purposes in accounting. Students find it difficult to use general English, which is possibly because of a lack of vocabulary. Furthermore, the researchers attempted to investigate this assumption further by using an online vocabulary test through the Oxford online vocabulary test with quantitative data analysis techniques. There were 233 tertiary students from 8 different classes who participated in this research, taking English for Accounting and English for Business as one of the courses in the first semester at Universitas Negeri Makassar. The tools for collecting data were the Oxford online vocabulary test, survey questionnaires, and observation. Quantitative data were used to collect data through questionnaires. The findings showed that the majority of respondents (38%) at the tertiary level were at A1 or the elementary English vocabulary level, which is inadequate to learn English for ESP at the university level. This research also found that the majority of respondents (50%) have learned English since elementary school which contradicts the vocabulary level test result. It can be concluded that students’ English vocabulary levels are insufficient for academic demands at the university level, particularly in preparing for ESP courses. Moreover, students’ vocabulary development shows inconsistent with the extended period of English learning since elementary with the increase of English vocabulary proficiency. However, integrating learning methods such as social media, online apps, website, games, movies, songs, and novels can be an effective approach for enhancing English learning in the classroom.